Proses Pendidikan Nabi Adam Perspektif al-Qur’an - Kustiana Arisanti (Jurnal Pendidikan Islam Indonesia, 2020)
Adam was the first human being whose taught by Allah SWT directly. Adam as the object of education and Allah SWT as the subject of education. The education process that is too simple is composed of several material which include teaching the names of all natural components, planting values and giving provision as the main manager of the earth, with its status as a caliph. The scientific transmission consists of scientific transmission from Allah SWT to the Prophet Adam as the caliph on earth and from the Prophet Adam to the Angel of God.